Absent in melanoma 2 inflammasome is required for host defence against Streptococcus pneumoniae infection. Issue 7 (October 2019) - Feng, Siwei; Chen, Tingting; Lei, Guihua; Hou, Fengqing; Jiang, Jiali; Huang, Qingyuan; Peng, Yuanyi; Ye, Chao; Hu, Dong-Liang; Fang, Rendong
Streptococcus pneumoniae, a leading cause of invasive pneumococcal disease, is responsible for high mortality and morbidity worldwide. A previous study showed that the NLR family pyrin domain containing 3 (NLRP3) and absent in melanoma 2 (AIM2) inflammasomes are essential for caspase-1 activation and IL-1β production in the host response to S. pneumoniae infection. The function of NLRP3 in host innate immunity to S. pneumoniae was studied in vivo and in vitro . However, the role of AIM2 in host defence against S. pneumoniae remains unclear. Here, we show that AIM2-deficient (AIM2 –/– ) mice display increased susceptibility to intra-nasal infection with S. pneumoniae in comparison to wild type mice and that this susceptibility was associated with defective IL-1β production. Macrophages from AIM2 –/– mice infected with S. pneumoniae showed impaired secretion of IL-1β as well as activation of the inflammasome, as determined by the oligomerisation of apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1 activation. Taken together, these results indicate that the AIM2 inflammasome is essential for caspase-1-dependent cytokine IL-1β production and eventual protection from pneumococcal infection in mice.